The Influence of Serum Prostate-Specific Antigen on the Accuracy of Magnetic Resonance Imaging Targeted Biopsy versus Saturation Biopsy in Patients with Previous Negative Biopsy. (11th October 2017) - Chang, Chao-Hsiang; Chiu, Hung-Chieh; Lin, Wei-Ching; Ho, Tzu-Lung; Chang, Han; Chang, Yi-Huei; Huang, Chi-Ping; Wu, Hsi-Chin; Yang, Chi-Rei; Hsieh, Po-Fan
Abstract : Objective . We compared the prostate cancer (PCa) detection rates of targeted biopsy (TB) and saturation biopsy (SB) in patients with previous negative biopsy and the accuracy of TB and SB stratified by different serum prostate-specific antigen (PSA) levels. Materials and Methods . Overall 185 patients were enrolled. In the magnetic resonance imaging (MRI) group, 65 men underwent TB and SB. In the control group, 120 men underwent SB alone. The primary outcome was the difference in PCa detection rate between the MRI group and control group. The secondary outcome was the difference in accuracy between TB and SB in detecting clinically significant PCa by stratifying the patients in the MRI group into those with PSA < 10 ng/ml and PSA ≥ 10 ng/ml. Results . The detection rates for overall and clinically significant PCa were higher in the MRI group than in the control group (46.2% versus 20.9% and 43.1% versus 16.7%, both p < 0.001 ). In the MRI group, the accuracy of TB was higher than SB (94.7% versus 84.2%, p = 0.001 ) for the patients with PSA ≥ 10 ng/mL. Conclusions . Combining TB and SB achieved the best cancer detection rate. The accuracy of TB was better than SB in the patients with serum PSA ≥ 10 ng/mL.